Deux voyages d’hiver - Etienne Barilier (Cahiers de Narratologie)
For an artist, the link between life and work is never a simple cause-effect relationship. The loving pain can be considered as the source of Schubert's Winterreise and of the Brahms Alto Rhapsody as well (the latter being based also upon a poem by Goethe, which tells also a winter journey). But these works transcend the life events from which they arise. Beyond the narcissism of the romantic self, they reflect two experiences of time, cyclical or progressive, and they tell two spiritual journeys. The pain of existence becomes a pure presence of life, and a purified story.